Lethal and behavioral effects of synthetic and organic insecticides on Spodoptera exigua and its predator Podisus maculiventris - Castro, Ancideriton Antonio de; Legaspi, Jesusa Crisostomo; Tavares, Wagner de Souza; Meagher, Robert L.; Miller, Neil; Kanga, Lambert; Haseeb, Muhammad; Serrao, Jose Eduardo; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola (Public Library Science, 2018)
Background The beet armyworm, Spodoptera exigua (Lepidoptera: Noctuidae), is a key insect pest of edible vegetables around the world and it is resistant to insecticide of different classes. Insecticides that are effective to this pest and selective to predator stinkbugs are required for the integrated management of S. exigua. Methods The toxicity of four commercial insecticide formulations azadirachtin + pyrethrin, spinosad, pyrethrin and chlorantraniliprole was tested on the target pest and their side effect were evaluated on the spined soldier bug, Podisus maculiventris (Heteroptera: Pentatomidae) through different bioassays. Results Spinosad and chlorantraniliprole were more toxic to S. exigua than to the predator P. maculiventris but opposite results were obtained for pyrethrin and azadirachtin + pyrethrin in contact toxicity bioassay. Chlorantraniliprole was the most toxic to S. exigua in oral toxicity bioassay, followed by spinosad, pyrethrin and azadirachtin + pyrethrin. Spinosad in oral toxicity bioassay was the most toxic to P. maculiventris, followed by pyrethrin, azadirachtin + pyrethrin and chlorantraniliprole. Spinosad caused irritability to the predator while pyrethrin to the pest. The insecticide repellency was not observed over the tested insect species. The synthetic insecticide chlorantraniliprole was less toxic than the natural pyrethrin, azadirachtin + pyrethrin and spinosad to the predator. Conclusions This work provides useful information on the combination of commercial insecticides with the predator P. maculiventris to controlling S. exigua in integrated pest management (IPM) programs.